Analisis Risiko dan Strategi Mitigasi Layanan Door To Door Pada Produk Pembiayaan Murabahah (Studi Kasus BMT Assyafi’iyah Berkah Nasional KC Metro) - Zahrotul Firdaus; Ika Trisnawati Alawiyah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze the risks and mitigation strategies implemented in the door-to-door service of murabahah financing products at BMT Assyafi’iyah Berkah Nasional, Metro Branch Office. The service is designed to improve financing accessibility for members, particularly micro-entrepreneurs; however, its implementation poses potential operational and financing risks. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that operational risks include limited field supervision, potential transaction recording errors, security risks for field officers, and high operational costs, while financing risks involve payment delays and an increase in Non-Performing Financing (NPF) due to members’ business instability. To mitigate these risks, BMT applies prudential principles through 5C analysis, multi-layered supervision, the use of an integrated Mobile Collection digital system, restrictions on large cash transactions, and a gradual mechanism for handling problematic financing. Overall, the study highlights that strengthening internal procedures and leveraging digital technology are key factors in maintaining the quality of murabahah financing and ensuring that the door-to-door service remains effective, secure, and compliant with sharia principles.